2024
DOI: 10.1186/s12909-024-05406-1
|View full text |Cite
|
Sign up to set email alerts
|

Medical, dental, and nursing students’ attitudes and knowledge towards artificial intelligence: a systematic review and meta-analysis

Hamidreza Amiri,
Samira Peiravi,
Seyedeh sara rezazadeh shojaee
et al.

Abstract: Background Nowadays, Artificial intelligence (AI) is one of the most popular topics that can be integrated into healthcare activities. Currently, AI is used in specialized fields such as radiology, pathology, and ophthalmology. Despite the advantages of AI, the fear of human labor being replaced by this technology makes some students reluctant to choose specific fields. This meta-analysis aims to investigate the knowledge and attitude of medical, dental, and nursing students and experts in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This study showed that only 32% of nurses and 39.1% of other healthcare professionals were completely or almost understood AI, and only 21.4% of nurses and 17.5% of healthcare professionals were completely or almost completely understood AI’s application in nursing, consistent with previous studies ( 44 ). In response to the general lack of awareness of AI among medical students and healthcare professionals, the level of awareness can be increased by incorporating AI into medical school curricula or by increasing AI-related training ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that only 32% of nurses and 39.1% of other healthcare professionals were completely or almost understood AI, and only 21.4% of nurses and 17.5% of healthcare professionals were completely or almost completely understood AI’s application in nursing, consistent with previous studies ( 44 ). In response to the general lack of awareness of AI among medical students and healthcare professionals, the level of awareness can be increased by incorporating AI into medical school curricula or by increasing AI-related training ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%